Cathepsin B- and L-like Protease Activities Are Induced During Developmental Barley Leaf Senescence - Igor A. Schepetkin; Andreas M. Fischer (Plants)
Leaf senescence is a developmental process allowing nutrient remobilization to sink organs. Previously cysteine proteases have been found to be highly expressed during leaf senescence in different plant species. Using biochemical and immunoblotting approaches, we characterized developmental senescence of barley (Hordeum vulgare L. var. ‘GemCraft’) leaves collected from 0 to 6 weeks after the onset of flowering. A decrease in total protein and ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) large subunits occurred in parallel with an increase in proteolytic activity measured using the fluorogenic substrates Z-RR-AMC, Z-FR-AMC, and casein labeled with fluorescein isothiocyanate (casein-FITC). Aminopeptidase activity detected with R-AMC peaked at week 3 and then decreased, reaching a low level by week 6. Maximal proteolytic activity with Z-FR-AMC and Z-RR-AMC was detected from pH 4.0 to pH 5.5 and pH 6.5 to pH 7.4, respectively, while two pH optima (pH 3.6 to pH 4.5 and pH 6.5 to pH 7.4) were found for casein-FITC. Compound E-64, an irreversible cysteine protease inhibitor, and CAA0225, a selective cathepsin L inhibitor, effectively inhibited proteolytic activity with IC50 values in the nanomolar range. CA-074, a selective cathepsin B inhibitor, was less potent under the same experimental conditions, with IC50 in the micromolar range. Inhibition by leupeptin and phenylmethylsulfonyl fluoride (PMSF) was weak, and pepstatin A, an inhibitor of aspartic acid proteases, had no effect at the concentrations studied (up to 0.2 mM). Maximal proteolytic activity with the aminopeptidase substrate R-AMC was detected from pH 7.0 to pH 8.0. The pH profile of DCG-04 (a biotinylated activity probe derived from E-64) binding corresponded to that found with Z-FR-AMC, suggesting that the major active proteases are related to cathepsins B and L. Moreover, immunoblotting detected increased levels of barley SAG12 orthologs and aleurain, confirming a possible role of these enzymes in senescing leaves.